I caratteri dell’indicibile. La traduzione del sintomo in alcune opere della letteratura sinofona - Pozzi, Silvia (L'ospite ingrato, 2025)
The trauma of the Cultural Revolution marks Chinese literary modernity, while Taiwanese identity is rooted in a historical memory shaped by national traumas. What challenges does the translator face? One risk is rationalization: how can one distinguish grammatical repetitions from rhetorical ones in Yu Hua’s Brothers? How can onomatopoeias, so frequent in Chinese, be preserved without creating alienating effects? Another challenge is cultural distance: in Owlish, Dorothy Tse reinvents Hong Kong. How can landscapes be made recognizable to readers with no geographical references? Finally, there is linguistic distance: in Kevin Chen’s Ghost Town, gui 鬼 means “ghost” but also “absurd” or “remote.” The novel also features linguistic layering, as the author uses Taiwanese – the maternal language of dreams and memories.